Influence De La Géomorphologie Sur La Distribution Spatiale Des Peuplements De Boscia Senegalensis (Pers.) Lam. Ex Poir. Dans La Commune Rurale De Simiri (Ouest Niger) - Habou, Rabiou; Abdoulaye, Diouf; Maârouhi, Inoussa Maman; Yakoubou, Bakasso; Mahamane, Saadou; Boubacar, Mamoudou Moussa; Sani, Idi Saidou; Abdou, Laouali; Ali, Mahamane (European Scientific Journal, ESJ, 2017)
B. senegalensis is a species with broad geographic distribution in the Sahel, especially in Niger, thanks to its special anatomical structures to withstand drought, high temperatures and poor soils. It presents and a heterogeneous distribution in the following areas topographic levels characteristic of the western Niger. This paper aimed to assess the distribution of B. senegalensis and its relationship with woody species through the description of the spatial structure of the point process following toposequences by Ripley’s method stands. The study highlighted the gregarious distribution of B. senegalensis and the close relationship between B. senegalensis and other species. Indeed, the species is in competition with other species on the plateau where water resources are scarce. But B. senegalensis tolerate these species on the slopes and in the shallows where water resources are relatively large.